'LET'S PET MY LEFT HAND LIKE IT IS PISCO, YEAH?' INTERPERSONAL TOUCH IN THE WORK OF ANDY INGAMELLS. (April 2022) - Kämper, Julian
Abstract: This article discusses touch-related works by the British composer–performer Andy Ingamells, works that that make up a large part of his oeuvre. In particular the article focuses on a series of works created during the last decade: Tape Piece (2012), The Ticklish Subject (2013), Having never seen (a) Ghost (2014), Waschen (2015), He That Plays The English Gentlemen Shall Be Welcome (2016), Petting Zoo (2019) and Petting Pisco (2020). These works exemplify Ingamells' understanding of music in general, but now, in the context of the COVID-19 pandemic, they can also be seen very differently as a commentary on social activities that people had to forego because of contact restrictions during the pandemic.